Causes of Stress Among Poles and How They Cope With Stress During the COVID-19 Pandemic - Twardowska-Staszek, Estera; Biel, Krzysztof; Rostek, Irmina; Seredyńska, Anna (Frontiers in Psychiatry, 2022)
This study aimed to learn about causes of stress among adult Poles and their ways of dealing with stress during the COVID-19 pandemic. A survey questionnaire was used, as well as two standardized research tools: Endler and Parker’s Coping Inventory for Stressful Situations (CISS), and Watson and Clark’s Positive and Negative Affect Schedule (PANAS). The research group comprised 595 people, including 80.5 % women. They were 18-75 years old. The most important stress factors were concern for one’s health, as well as the current political and economic situation in the country. Most of the participants lean towards avoidance-oriented coping with stress, fewer of them prefer emotion-oriented coping, and the remaining ones focus on task-oriented coping. Task-oriented style is typical of those who are older, married and those who have children. Emotion-oriented coping is more common among women, young people, unmarried people and those without children. Avoidance-oriented style is connected with those who are single, childless, and combining study with work. The most adaptive styles of dealing with stress in terms of emotions included task-oriented coping and social diversion. Psychological support focused on strengthening adaptive strategies of coping with stressful situations is an important task for professionals in the field.